[OP.4B.05] MIR-30A-3P EXPRESSION IN THE HEARTS OF DIABETIC RATS: EFFECTS OF ANGIOTENSIN TYPE 1 (AT1) AND ANGIOTENSIN TYPE 2 (AT2) RECEPTORS. (September 2017) - Castoldi, G.; Di Gioia, C.; Roma, F.; Carletti, R.; Sinico, R.A.; Stella, A.; Zerbini, G.; Perseghin, G.
Abstract : Objective: Compound 21 (C21), a selective AT2 receptor agonist, showed cardioprotective effects in experimental model of hypertension. miRNAs, small non-coding RNAs, play an important role in the control of gene expression. The aim of this study was to evaluate the effect of Compound 21 on miR-30a-3p expression in the hearts of Zucker diabetic fatty (ZDF) rats (type 2 diabetes). Design and method: The experiments lasted 15 weeks (from 5 to 20 weeks of age) and were performed in ZDF rats (n = 21) and in control Lean rats (n = 8). ZDF rats were divided into 3 groups: 8 ZDF rats were treated with C21 (0.3 mg/kg/day, i.p.); 5 ZDF rats were treated with losartan (10 mg/kg/day in drinking water), and 8 ZDF rats were maintained without treatment. Blood glucose level, body weight and blood pressure (tail-cuff) were measured every 4 weeks and at the end of the protocol. At 20 weeks of age rats were sacrificed and hearts were excised. The apex of the heart was frozen in liquid nitrogen for the evaluation of myocardial miR-30a-3p expression (real-time PCR), and the remaining part of the heart was fixed with 10% formalin for histomorphometric analysis. Results: ZDF rats showed high blood glucose values (p < 0.0001 vs. control Lean rats), that were not modified by C21 or losartan treatment. No changes in blood pressure were observed in ZDF rats as compared to control Lean rats. C21 did not modify blood pressure, while losartan treatment caused a significant decrease respect to the other groups (p < 0.05). Myocardial miR-30a-3p expression was higher in ZDF rats as compared to control Lean rats (p < 0.01). C21 administration or losartan treatment decreased miR-30a-3p (p < 0.01). Gene ontology analysis showed an involvement of miR-30a-3p in ECM receptor interaction and PI3K-AKT signalling pathways. Conclusions: These data demonstrate that AT2 receptor activation or AT1 receptor blockade modulate miR-30a-3p expression in ZDF rats, suggesting a role for miR-30a-3p in myocardial remodelling in diabetes.